Sensory and spinal inhibitory dorsal midline crossing is independent of Robo3 - Comer, John D.; Pan, Fong Cheng; Willet, Spencer G.; Haldipur, Parthiv; Millen, Kathleen J.; Wright, Christopher V. E.; Kaltschmidt, Julia A. (Frontiers in Neural Circuits, 2015)
Commissural neurons project across the midline at all levels of the central nervous system, providing bilateral communication critical for the coordination of motor activity and sensory perception. Midline crossing at the spinal ventral midline has been extensively studied and has revealed that multiple developmental lineages contribute to this commissural neuron population. Ventral midline crossing occurs in a manner dependent on Robo3 regulation of Robo/Slit signaling and the ventral commissure is absent in the spinal cord and hindbrain of Robo3 mutants. Midline crossing in the spinal cord is not limited to the ventral midline, however. While prior anatomical studies provide evidence that commissural axons also cross the midline dorsally, little is known of the genetic and molecular properties of dorsally-crossing neurons or of the mechanisms that regulate dorsal midline crossing. In this study, we describe a commissural neuron population that crosses the spinal dorsal midline during the last quarter of embryogenesis in discrete fiber bundles present throughout the rostrocaudal extent of the spinal cord. Using immunohistochemistry, neurotracing, and mouse genetics, we show that this commissural neuron population includes spinal inhibitory neurons and sensory nociceptors. While the floor plate and roof plate are dispensable for dorsal midline crossing, we show that this population depends on Robo/Slit signaling yet crosses the dorsal midline in a Robo3-independent manner. The dorsally-crossing commissural neuron population we describe suggests a substrate circuitry for pain processing in the dorsal spinal cord.